Implementation of a Biocircuit Implants for Neurotransmitter Release During Neuro-Stimulation - Ly, Suw Y.; Choi, Dal woong (Current Neurovascular Research, 2013)
Neurotransmitter assay of epinephrine (EP) was sought using a modified carbon nanotube paste electrode (PE). Using optimum conditions, cyclic voltammetry (CV) and the square wave (SW) stripping voltammetric working ranges were attained to 10-100 mgL-1 (CV) and 20-140 ngL-1 (SW). The relative standard deviation of 0.0549 (n=15) was obtained at 20.0 mgL-1 EP constant. Here, the analytical detection limit (S/N) was reached with 4.60 ngL-1 (2.5×10-11 molL-1) EP. The hand-made electrode was implanted into the in-vivo brain core of the animals and was used in chronoamperometric neuro detection. The results obtained are applicable in neuro sensing, physiological control, and other neuroscience fields.
Keywords: interface